SOCIO-DEMOGRAPHIC, SOCIAL ECONOMIC AND SOCIO- CULTURAL FACTORS THAT INFLUENCES UPTAKE OF CERVICAL CANCER SCREENING SERVICES IN LOW RESOURCE SETTINGS - Mwangi, H. J.; Gachau, G. A.; Kabiru, W E. (Global Journal of Health Sciences, 2017)
Background: Cervical cancer is the fourth commonest cancer in women and the seventh overall, with estimated 528,000 new cases every year. Around 85% of the global burden occurs in the low resource settings where it accounts for almost 12% of all female cancers. In these areas programmes for screening and treatment are deficient or underutilized. This is even after the services are availed or assumed to be provided. Objectives: To establish socio-demographic, social economic and socio- cultural factors that influences uptake of cervical cancer screening services in Kitui Central Sub County, Kenya. Methodology: A descriptive cross-sectional study design was done; where women of reproductive age attending MCH/FP clinic in public health facilities were systematically randomly selected and exit interview was the main data collection technique. Key informants were also interviewed. Results: A total of 370 women of reproductive age were interviewed. Majority,(69.2%) were aged below 29 years, more than 80% had completed their primary school education,68% were married,57% were protestants,75 % were having three children or less,61% were depending on farm produce and more than 60% were earning less Ksh 5000 per month..There was statistical significant association between utilization of VIA/VILI cervical cancer screening services and the level of education(=21.728,df=3,p= 0.000),main source of income.(= 15.030,df=2,p=0.01),average monthly income, (=27.942, df=4, p=0.0001), main decision maker in the family, (=6.908, df=2, p=0.032). Public Health facilities were not well staffed and equipped to adequately offer the VIA/VILI screening services effectively. Conclusion: The level of awareness on cervical cancer prevention was low and this among other factors lead to low VIA/VILI screening tests utilization. We recommend strategies to be put into place to increase awareness on available methods of screening and importance of being screened for cervical cancer among eligible women.